P-106 CAN POOR ORAL HYGIENE BE RESPONSIBLE FOR MESH INFECTION FOLLOWING HERNIA REPAIR? A SYSTEMATIC REVIEW AND SUGGESTION FOR NEW PRACTICE. (13th October 2022) - East, B; Podda, M; Beznosková-Seydlová, M; de Beaux, A C
Abstract: Background: There is a reasonable evidence around oral/dental health and implant infection in orthopaedic and cardiovascular surgery. Mesh hernia repair is another area of surgical practice associated with a permanent implant. The aim of this SR was to review the evidence around oral/dental health and mesh infection. Mehods: The study was registered at Prospero. A systematic review of the literature was undertaken according to the PRISMA2020 statement. The initial search identified 520 publications. After a review by title and abstract, 40 papers were read in full text. A further 4 papers were identified from references and searching.15 publications were included in the final review. Results: There is no published evidence investigating the state of oral hygiene/health and the risk of mesh infection. Improvement in oral hygiene/health can reduce surgical site infection and implant infection in colorectal, gastric, liver, orthopaedic and cardiovascular surgery. Poor oral hygiene/health is associated with a large increase in oral bacteria and bacteraemia on everyday activities such as when chewing or brushing teeth. Antibiotic prophylaxis does not appear to be necessary before invasive dental care in patients with an implant. Conclusion: Good oral hygiene and oral health is a strong public health message. The effect of poor oral hygiene on mesh infection and other complications of mesh hernia repair is unknown. While research is clearly needed in this area, extrapolating from evidence in other areas of surgery where implants are used, good oral hygiene/health should be encouraged amongst hernia patients both prior and after their surgery.